Heat stress impairs repeated jump ability after competitive elite soccer games - Mohr, M.; Krustrup, P. (The Journal of Strength and Conditioning Research, 2013)
This study examined the effect of environmental heat stress on repeated jump performance after elite competitive soccer games. Male elite soccer players (n = 19) from 2 Scandinavian teams participated (age: 26.7 ± 1.0 years, height: 181.7 ± 1.1 cm, body mass: 75.8 ± 1.0 kg). The players had a Yo-Yo IR2 performance of 1,032 ± 42 m (range: 920-1,400 m). The players took part in the Champions League Qualification, where 6 games (3 home and 3 away) were played. The home games took place at an average ambient temperature of 12.2 ± 0.5° C (control game; CON) and the away games in hot conditions (30.0 ± 0.3° C; HOT). In the resting condition (Baseline) and immediately after CON and HOT, the players performed a repeated countermovement jump (CMJ) test consisting of 5 jumps separated by 5 seconds of recovery. Game-induced body mass loss was determined based on change in body mass after correction for fluid intake. The net loss of body mass was 3.1 ± 0.3% in HOT, which was higher (p < 0.05) than in CON (1.7 ± 0.2%). Mean CMJ performance after HOT was 37.9 ± 1.1 cm, which was 6.0% lower (p < 0.05) than Baseline (40.3 ± 1.1 cm) and tended (p = 0.08) to be lower than in the CON (39.6 ± 1.2 cm). The mean CMJ performance after CON was not different from Baseline. Peak CMJ performance after HOT was 41.1 ± 1.1 cm, which was not different from either Baseline or CON (42.0 ± 1.1 and 41.7 ± 1.2 cm, respectively). The relative decline in repeated CMJ performance from Baseline to after HOT correlated (r = 0.60; p < 0.05) to relative net loss in body mass during HOT. This study demonstrates that repeated CMJ performance deteriorates after a soccer game played in warm environmental settings, which is partly associated with severe dehydration.